2-year seismological experiment near Fagradalsfjall, Reykjanes peninsula in 2021/22 - Eibl, Eva P.S.; Hersir, Gylfi P.; Gudnason, Egill Á.; Petursson, Fridgeir (GFZ Data Services, 2022)
Abstract "2-year seismological experiment near Fagradalsfjall, Reykjanes peninsula in 2021/22" is a two-year seismological experiment realized near the eruptive site at Fagradalsfjall on the Reykjanes peninsula, Iceland, by Eva Eibl (University of Potsdam) in collaboration with Gylfi P. Hersir, Egill Á. Gudnason and Friðgeir Pétursson from ISOR Iceland. From March to September 2021 an effusive, basaltic eruption happened in Geldingadalir near mount Fagradalsfjall on the Reykjanes peninsula. The aim of the seismic experiment was to monitor volcano-seismic signals such as LP events, VT events and tremor, before, during and after the eruption from 14 March 2021 to August 2022. We used two broadband seismometers (Nanometrics Trillium Compact 120 s) and two rotational sensors (iXblue blueSeis-3A) and stored the data on DataCubes and CommunicationCubes, respectively. Sensors were until mid-June installed on the surface and shielded from wind using a bucket. From mid-June they were buried 40cm deep in the ground at about 2 km from the eruptive vent. At any given time, at least one station recorded the seismic signals caused by the eruption. Waveform data are available from the GEOFON data centre, under network code 9F.